A‐activated protein kinase is required for cell survival and growth in hela‐s3 cells in vivo. Issue 6 (11th June 2014) - Song, Xuhong; Huang, Dongyang; Liu, Yanmin; Pan, Xiaokang; Zhang, Jing; Liang, Bin
Abstract Activation of the AMP‐dependent protein kinase (AMPK) is linked to cancer cell survival in a variety of cancer cell lines, particularly under conditions of stress. As a potent activator of AMPK, metformin has become a hot topic of discussion for its effect on cancer cell. Here, we report that AMPK activated by metformin promotes HeLa‐S3 cell survival and growth in vivo. Our results show that metformin inhibited cell proliferation in MCF‐7 cells, but not in LKB1‐deficient HeLa‐S3 cells. Re‐expression of LKB‐1 in HeLa‐S3 cells restored the growth inhibitory effect of metformin, indicating a requirement for LKB‐1 in metformin‐induced growth inhibition. Moreover, AMPK activation exerted a protective effect in HeLa‐S3 cells by relieving ER stress, modulating ER Ca2+ storage, and finally contributing to cellular adaptation and resistance to apoptosis. Our findings identify a link between AMPK activation and cell survival in HeLa‐S3 cells, which demonstrates a beneficial effect of AMPK activated by metformin in cancer cell, and suggests a discrete re‐evaluation on the role of metformin/AMPK activation on tumor cell growth, proliferation, and on clinical application in cancer therapy. © 2014 IUBMB Life, 66(6):415–423, 2014